(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Traditionally, pterosaurs have been included within the Archosauriformes and many contemporary workers consider the Pterosauria the sister group to Lagosuchus, Scleromochlus and the Dinosauria. New analyses cast doubts on those relationships because nearly all presumed archosauriform or ornithodire "synapomorpies" are either not present within the Pterosauria or are also present within certain prolacertiform taxa. Recent examinations of the holotypes of Cosesaurus aviceps, Longisquama insignis and Sharovipteryx mirabilis suggest that many characters may be interpreted differently than previously reported. Results of several subsequent cladistic analyses suggests that these "enigmatic" prolacertiforms, along with the newly described Langobardisaurus, are sister taxa to the Pterosauria, based on a suite of newly identified synapomorphies.